2004
DOI: 10.1021/bm049949u
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Degradation of Poly(amino acid)s

Abstract: Natural poly(amino acid)s are a group of poly(ionic) molecules (ionomers) with various biological functions and putative technical applications and play, therefore, an important role both in nature and in human life. Because of their biocompatibility and their synthesis from renewable resources, poly(amino acid)s may be employed for many different purposes covering a broad spectrum of medical, pharmaceutical, and personal care applications as well as the domains of agriculture and of environmental applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
96
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(99 citation statements)
references
References 113 publications
0
96
0
Order By: Relevance
“…Similar to CphB, the extracellular CGPases CphE Pa and CphE Bm , from Pseudomonas anguilliseptica B1 and Bacillus megaterium BAC19, respectively, were identified as serine-type CGP-specific enzymes and produced mainly CGP dipeptides as degradation products. Labeling studies of CphE Pa showed that the enzyme hydrolyzes CGP at the carboxyl terminus and successively releases ␤-AspArg dipeptides from the degraded polymer chain end (30). Moreover, extracellular CGPases were also found in strictly and facultatively anaerobic bacteria, such as Sedimentibacter hongkongensis KI and Pseudomonas alcaligenes DIP1, respectively (31,36).…”
mentioning
confidence: 99%
“…Similar to CphB, the extracellular CGPases CphE Pa and CphE Bm , from Pseudomonas anguilliseptica B1 and Bacillus megaterium BAC19, respectively, were identified as serine-type CGP-specific enzymes and produced mainly CGP dipeptides as degradation products. Labeling studies of CphE Pa showed that the enzyme hydrolyzes CGP at the carboxyl terminus and successively releases ␤-AspArg dipeptides from the degraded polymer chain end (30). Moreover, extracellular CGPases were also found in strictly and facultatively anaerobic bacteria, such as Sedimentibacter hongkongensis KI and Pseudomonas alcaligenes DIP1, respectively (31,36).…”
mentioning
confidence: 99%
“…CGP accumulation is promoted by several conditions, including phosphorus limitation (46), sulfur limitation (5), low temperature, low light intensity, or a combination of these factors (32), and in the presence of translational or transcriptional inhibitors (3,13). CGP functions as a temporary nitrogen, energy, and possibly carbon reserve (12,26).…”
mentioning
confidence: 99%
“…Furthermore, CGP proved to be highly resistant to many proteases and arginase (45,47). Therefore, CGPases probably evolved as specialized enzymes for the purpose of degrading CGP under certain environmental conditions (30,32,39). CGP is a widespread biopolymer that represents a valuable source of nitrogen, carbon, and energy and probably occurs in many habitats (see the spectrum of CGP-producing organisms mentioned above).…”
mentioning
confidence: 99%